Critical Discourse Analysis: English as It Is Learned and Treated in Asia - Eka Listianing Rahayu (English Learning Innovation (englie), 2023)
The English language teaching in Indonesia and some other ASEAN countries seem problematic. It can be seen from the low English proficiency of many school graduates despite years of learning English. Therefore, in the recent years, there has been a need of a new breakthrough in the English curriculum by considering local cultures and values so the English taught in schools is more contextual, practical and suits the local needs and usage. The curriculum is expected to reflect the English norms as a lingua franca in Asia, and not imposing native speakerism. This paper analyzes a newspaper article discussing how English is learned and treated in Asia, which was published in the Jakarta Globe, a popular local English newspaper. The analysis seeks further understanding on the discursive field of English, particularly in Asian context. Using Fairclough’s (2001) framework encompassing three stages (description - interpretation – explanation), this paper analyzes both macro and microstructure of the texts. The macrostructure is dealing with the ideology constructed in the texts, while the microstructure comprises the formal property or linguistic components. With these definitions, this critical discourse analysis (CDA) looks to find connections between microstructures of the text and the macro structures of social institutions and societies where the texts are distributed and consumed. From these three stages of critical discourse analysis, it was found that English is often portrayed as a prestigious language by using specific labels and metaphors. Besides, the ideology of “standard” and “monolithic view” of English is commonly imposed, and thus influences the English language teaching in Asia.